Synthesis, Characterization and Biological Evaluation of 1, 2-Disubstituted Benzimidazole Derivatives using Mannich Bases - B. Anil Reddy (E-Journal of Chemistry)
The ring system in which a benzene ring is fused to the 4,5-positions of imidazole is designated as benzimidazole. Condensations of 2-substituted benzimidazole derivatives were synthesized by different carboxylic acids using Mannich base and anti-inflammatory activity. The various positions on the benzimidazole ring are numbered in the manner indicated with the imino function as number one. The formations of the product were conformed by the analytical and spectral data.